Wireless Positioning: Principles and Practice - Sharp, Ian; Yu, Kegen (Navigation: Science and Technology,, 2019)
This book focuses on non-GNSS positioning systems and approaches. Although it addresses both theoretical and practical aspects, the primary focus is on engineering practice. This is achieved by providing in-depth studies on a number of major topics such as tracking system architecture, link budget, system design, implementation, testing, and performance evaluation. It studies four positioning application cases in detail: covert vehicle tracking, horse racing, rowing, and tracking for field sports. Its comprehensive and systematic treatment of practical issues in wireless positioning makes the book particularly suitable for readers who are interested in learning about practical wireless positioning solutions. It will also benefit researchers, engineers and graduate students in fields such as positioning and navigation, geospatial engineering and telecommunications.